Clinical and epidemiological profile of pancreatic cancer in Paraná between 2010 and 2018 (Research, Society and Development, 2023)
Pancreatic cancer represents the 5th neoplasm that most kills women and the 7th with the highest mortality among men in Brazil. Despite being in 10th place in the ranking of cancer incidence in the country, its high morbimortality and increasing rates project it as a leading cause of death by 2050. The absence of specific symptoms, effective screening strategies and Competent treatments make pancreatic cancer a public health challenge. Risk factors may include advanced age, obesity, alcoholism, diabetes and genetic predisposition syndromes, but studies regarding these are still insufficient to characterize this profile. The objectives of this study were to characterize the clinical profile of patients with pancreatic cancer, helping to delineate risk factors for neoplasia. Data were obtained from the INCA hospital cancer registry platform, selecting patients with pancreatic cancer registered between 2010 and 2018 treated in Paraná, analyzing the characteristics: gender, ethnicity, educational level, age group, tobacco consumption and of alcohol, anatomopathological sublocation. The most prevalent non-modifiable characteristics were white, incomplete primary education, male, age group 60-64 years; modifiable variables, never smokers and never drinkers; the head of the organ was the most affected region. There was also a high rate of cases without information about the characteristics in the hospital records. From the characterization of the patients, it will be possible to help guide strategies for identification, support and treatment of pancreatic cancer.